Slovak Republic : 2010 Article IV Consultation-Staff Report ; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund (Washington, D.C. : International Monetary Fund, 2010)
1. The economy is emerging from a deep recession. Real GDP declined by 4.7 percent in 2009, following a collapse in the first quarter and recovery throughout the rest of the year, which continued into 2010. Though starting later, the initial drop in real GDP was larger than in most of Slovakia's neighbors. But the recovery also has been more pronounced-year-on-year growth in the first and second quarters of 2010 was near 5 percent, the highest in the EU. At 1 percent in July 2010 (year-on-year), inflation is significantly below the euro area average.
Keywords: Slovakia; Slovakia; Electronic books